Intricate interplay of CRISPR-Cas systems, anti-CRISPR proteins, and antimicrobial resistance genes in a globally successful multi-drug resistant Klebsiella pneumoniae clone - Jianping Jiang; Astrid V. Cienfuegos-Galletd; Tengfei Long; Gisele Peirano; Tingyu Chu; Johann D. D. Pitout; Barry N. Kreiswirth; Liang Chen (Genome Medicine)
Abstract Background Klebsiella pneumoniae is one of the most prevalent pathogens responsible for multiple infections in healthcare settings and the community. K. pneumoniae CG147, primarily including ST147 (the founder ST), ST273, and ST392, is one of the most globally successful MDR clone linked to various carbapenemases. Methods One hundred and one CG147 strains were sequenced and additional 911 publicly available CG147 genome sequences were included for analysis. The molecular epidemiology, population structure, and time phylogeny were investigated. The virulome, resistome, and mobilome were analyzed, and the recombination in the capsular region was studied. The CRISPR-Cas and anti-CRISPR were identified. The interplay between CRISPR-Cas, anti-CRISPR, and carbapenemase-encoding plasmids was analyzed and experimentally validated. Results We analyzed 1012 global CG147 genomes, with 80.4% encoding at least one carbapenemase (NDM [529/1012, 52.3%], OXA-48-like [182/1012, 17.7%], and KPC [105/1012, 10.4%]). Surprisingly, almost all CG147 strains (99.7%, 1009/1,012) harbor a chromosomal type I-E CRISPR-Cas system, with 41.8% (423/1012) containing an additional plasmid-borne type IV-A3 CRISPR-Cas system, and both target IncF plasmids, e.g., the most prevalent KPC-encoding pKpQIL-like plasmids. We found the presence of IV-A3 CRISPR-Cas system showed a negative correlation with the presence of KPC. Interestingly, a prophage-encoding anti-CRISPR AcrIE8.1 and a plasmid-borne anti-CRISPR AcrIE9.2 were detected in 40.1% (406/1012) and 54.2% (548/1012) of strains, respectively, which displayed positive correlations with the presence of a carbapenemase. Plasmid transfer experiments confirmed that the I-E and IV-A3 CRISPR-Cas systems significantly decreased (p < 0.001) KPC-encoding pKpQIL plasmid conjugation frequencies, while the AcrIE8.1 and AcrIE9.2 significantly increased (p < 0.001) pKpQIL conjugation frequencies and protected plasmids from elimination by CRISPR-Cas I-E system. Conclusions Our results indicated a complex interplay between CRISPR-Cas, anti-CRISPR, and mobile genetic elements that shape the evolution of CG147. Our findings advance the understanding of multi-drug resistance mechanisms and will aid in preventing the emergence of future MDR clones.